Efeitos da administração de derivado de 1,4-diidropiridina em resposta ao estresse oxidativo induzido em Caenorhabditis elegans - Cardoso, Ronan Martins (2020)
Aging is a progressive process in the life of an organism and can lead to the deterioration of tissues, cell integrity and organ failure. It is in this phase of life that there is more evidence of vulnerability, chronic illness and death. The oxidative stress hypothesis proposes that aging is conditioned by the increase in reactive oxygen species (ROS) in the body, since natural antioxidants decrease their function as you get older. The estimate for 2050 is that more than 20% of the population is 60 years old or older. In this context, the search for antioxidant compounds that play a role in the prevention and treatment of age-related diseases is important. Quinoline is a nitrogen heterocyclic, which was first obtained from coal tar in 1834, and can play antioxidant and longevity function. In this sense, the objective was to evaluate the effects of ethyl 2,7,7-trimethyl-5-oxo-4-phenyl-1,4,5,6,7,8-hexahydroquinoline-3-carboxylate (QUI 1), derived from 1,4-dihydropyridine, on survival and longevity in strains N2 and glp-4; sek-1 from Caenorhabditis elegans, in addition to antioxidant and antibacterial activity. For that, the nematodes were treated with concentrations of 100, 250 and 500 μg/ml of QUI 1 and DMSO for control. In early adulthood, they were induced to thermal stress (35ºC), osmotic stress (500 mM NaCl) and hydrogen peroxide (0.3% H2O2), and for longevity analysis the nematodes were evaluated until all were dead. The analysis of the longevity, H2O2-induced and thermal stress tests was performed using the Kaplan-Meier survival curve and the differences between groups analyzed by the log-rank test, while the behavioral analysis of the pharyngeal pumping rate and the osmotic stress test by the Anova Two Way test and the comparison between groups by the post hoc tests by Sidak and Bonferroni, respectively. The tests were analyzed using the GraphPad Prism v.8.0.2 software with a pre-established significance level of p<0.05. QUI 1 showed antioxidant activity with an IC50 of 556.94 ± 3.40 g / mL-1 at its highest concentration used. As for antibacterial activity, E. coli bacteria (OP50) were resistant to the compound without the formation of a halo. No significant results were found for the analyzed stress and longevity tests. In conclusion, no evidence was found that treatment with QUI 1 influenced the longevity and resistance to stress induced in C. elegans.